Development of a Louver Movement Mechanism for a Prototype of an Adaptive Dynamic Facade - Lukman Afif; Muhammad Sega Sufia Purnama (Program Studi Arsitektur, Fakultas Teknik, Universitas Riau, 2026)
Dynamic façades are an approach to adaptive building design that enables façade elements to actively respond to changing environmental conditions. The successful implementation of dynamic façades is determined not only by their environmental performance but also by the reliability of the movement mechanisms employed. However, studies on the mechanization of dynamic façades remain relatively limited compared to research focusing on thermal and daylighting performance. This study aims to develop and evaluate louver movement mechanisms in a dynamic façade prototype using stepper motors as the driving system. The research adopted a design development research approach, encompassing louver design development, material selection, mechanism development, prototype fabrication, and system evaluation. Two mechanization approaches were tested: a belt-driven system and a one motor-one-louver system. The evaluation considered movement performance, mechanical load distribution, ease of maintenance, and operational constraints. The results indicate that the belt-driven system generated higher mechanical loads, resulting in less optimal louver movement, whereas the one motor-one-louver system provided more even load distribution and more stable movement. These findings provide design lessons learned that may serve as references for the development of kinetic and adaptive façades in tropical buildings.